(untitled) (SCIÉNDO INGENIUM, 2024)
In the present investigation, mixtures of asphalt material with percentages of disused tires in the form of granulated rubber at 1% and 2% were evaluated. Likewise, a conventional mixture of asphalt material was made, used as a standard within the study. The research methodology is applied, with a quantitative approach and a pure experimental design. The method applied is deductive at an explanatory level. In the process, the necessary quantities of each of the materials are considered, using the Marshall Method for the design of asphalt mixtures. Likewise, the mixtures were subjected to temperature changes, reaching 145 °C in order to be molded. In relation to the percentage of voids, the three designs meet the requirements of the EG-2013 regulations: (0%) = 4.3, (1%) = 4.4, (2%) = 3.8. Regarding stability, the standard mixture has a stability of 1918.7 kg; however, the mixture with the addition of 1% granulated rubber reaches a stability of 1986.7 kg. Therefore, the stability of the improved sample exceeds that of the mixture by 3.5%. It is concluded that the optimal percentage of granulated rubber is 2%. It is concluded that the optimal percentage of granulated rubber is 2%.